Carl's sleepy afternoon - Day, Alexandra (New York, NY : Farrar Straus Giroux, 2005)
Rather than take an afternoon nap, Carl spents the afternoon visiting friends in town while his owner is out shopping.
9 13 18 19
Keywords: Dogs -- Fiction